METAPHORICAL MEANINGS INSIDE OF DISCOURSE OF PRESIDENT, PARLIAMENT, AND MAJOR NATIONAL ELECTION 2014 - Pristiwati, Rahayu; Rustono, Rustono; Rokhman, Fathur; Mardikantoro, Hari Bakti (The Journal of Educational Development, 2016)
This article aimed to describe metaphorical utterance meaning inside of discourse of president, parliament, and major national election 2014. The approach used was a qualitative descriptive approach. The data was the extract of the campaign discourse. The data analysis was done by using a normative method, referential method, and reflective introspective method. The meaning of metaphorical extension inside of the campaign based on comparative theory were (1) objects to refer things, (2) objects to refer situation, (3) objects to refer action, (4) place to refer place, (5) place to refer situation, (6) action to refer action, (7) action to refer situation, (8) situation to refer situation, (9) situation to refer action, and (10) time to refer time. Metaphorical meaning based on interactive theory covers the meaning of metaphorical utterances which changes its meaning into directive meaning tended to or reverse.